Threader - Turner, Rebekah (Sydney, New South Wales : Harlequin Teen, 2016)
Welcome to the Helios Academy: evolve or die It's the year 2050 and life is increasingly hard for 'non-citizens'. A slowly emerging young minority has been exposed as 'talents'; they harbour mutations that give them special gifts - super strength, regenerative powers, psychic gifts or the ability to sink through shadows and travel through time and space. As governments unite to form a global talent registry and powerful corporations step in to take control, a 'talent' can be a passport to citizenship and a better life, but there is a cost as Josie Ryder is about to discover. Orphaned at six, Josie Ryder has been raised by her uncle. Her talent is an unusual one: she is a threader, able to weave a combination of psychic talents around others to manipulate their powers. Working in her uncle's antique store and dreaming of a better life, Josie has done everything to keep a promise to her late father: stay off the global talent registry and keep her talents hidden. But as Josie tries to make ends meet with the occasional illegal act, she risks a third strike with local law enforcement and, desperate for a better life, Josie finally breaks her promise to her father's memory and sends an enquiry to the prestigious Helios Academy, a training facility in a distant country for talents. When the Helios Academy respond by sending mysterious slider, Blake Galloway to extract Josie, then offer her a position at their select and highly competitive institution, things begin to get really interesting, and more than a little dangerous....
Imprint: Harlequin Teen.
Vendor-supplied metadata
Keywords: Juvenile Fiction - Action & Adventure; Gifted persons -- Juvenile fiction; Psychic ability -- Juvenile fiction; Gifted persons; Mutation (Biology); Psychic ability; Mutation (Biology) -- Juvenile fiction; Young adult fiction; Australian; Electronic books; Fantasy fiction